APLIKASI SANDI PRAMUKA BERBASIS ANDROID MENGGUNAKAN FRAMEWORK PHONEGAP (Information Technology and Telematics, 2014)
ABSTRACT Learning Scout encoding is often done indoors or outdoors with a considerable number of participants with the help of a book or chalkboard. The method causes less interested scouts and difficulty in understanding the material presented. The goal of this research is to develop a scouts password applications based on Android using Phonegap framework. So that would make it easier for scouts to learn the Scouts password wherever and whenever as long as they carry a smartphone or android tablet with this application installed in it. The results of this research are Scout password application can run using android device. This application is created using the programming language HTML, CSS, JavaScript and using Phonegap framework to build the application. As for the quiz feature exploit jQuizMe plug-in. Keywords: scout password , android applications, Phonegap.